Lyman-alpha wing absorption in cool white dwarf stars - Rohrmann, Rene Daniel (2011)
Kowalski & Saumon identified the missing absorption mechanism in the observed spectra of cool white dwarf stars as the Lyman α red wing formed by the collisions between atomic and molecular hydrogen and successfully explained entire spectra of many cool DA-type white dwarfs. Owing to the important astrophysical implications of this issue, we present here an independent assessment of the process. For this purpose, we compute free–free quasi-molecular absorption in Lyman α due to collisions with H and H2 within the one-perturber, quasi-static approximation. Line cross-sections are obtained using theoretical molecular potentials to describe the interaction between the radiating atom and the perturber. The variation in the electric dipole transition moment with the interparticle distance is also considered. Six and two allowed electric dipole transitions due to H–H and H–H2 collisions, respectively, are taken into account. The new theoretical Lyman α line profiles are then incorporated in our stellar atmosphere program for the computation of synthetic spectra and colours of DA-type white dwarfs. Illustrative model atmospheres and spectral energy distributions are computed, which show that Lyman α broadening by atoms and molecules has a significant effect on the white dwarf atmosphere models. The inclusion of this collision-induced opacity significantly reddens spectral energy distributions and affects the broad-band colour indices for model atmospheres with Teff < 5000 K. These results confirm those previously obtained by Kowalski & Saumon. Our study points out the need for reliable evaluations of H3 potential energy surfaces covering a large region of nuclear configurations, in order to obtain a better description of H–H2 collisions and a more accurate evaluation of their influence on the spectrum of cool white dwarfs.